Justicia distributiva y reconocimiento. Una expansión de la propuesta de Honneth (Andamios, Revista de Investigación Social, 2011)
Axel Honneth’s normative model of recognition has had growing influence in contemporary discussions. The theoretical scope of his proposal is wide enough to integrate questions of distributive justice; however, the treatment that Honneth gives to those questions is not intensive enough as he does not consider, among other things, the problem of the informational basis. On the other hand, Amartya Sen’s capabilities approach has some points in contact with Honneth’s proposal, which would enable the informational basis of the capabilities approach to be incorporated into a new proposal that would have the autonomy of reciprocal recognition as its background. These coincidences would allow for the solution to some of the difficulties and weaknesses that Sen’s programme, as well as Honneth’s one has, by means of a programme of distributive justice that incorporates both.
Keywords: Justice; recognition; distribution; capabilities; vulnerability